Factors relating to social isolation in urban Japanese older people: A 2-year prospective cohort study. (January 2020) - Takahashi, Tomoya; Nonaka, Kumiko; Matsunaga, Hiroko; Hasebe, Masami; Murayama, Hiroshi; Koike, Takashi; Murayama, Yoh; Kobayashi, Erika; Fujiwara, Yoshinori
Highlights: We examined the social, mental and physical factors relating to social isolation. We found factors relating to the onset of social isolation in older people. We also found factors relating to recovery from social isolation in older people. Abstract: Purpose: We analyzed the data from a 2-year prospective-cohort survey to identify factors relating to new incidences of social isolation and recovery from social isolation in community-dwelling older people. Materials and methods: We conducted a longitudinal study (2013–2015) involving 2657 older residents of Iriarai, Japan. A chi-square test, an independent t -test, and logistic regression analysis with imputed data were conducted to examine categorical data, continuous variables, and factors relating to social isolation, respectively. Principal results: The results suggested that the factors that predicted future social isolation included being a man, being older, living with others, having a decline in mental health, having a lower frequency of going out, and not participating in community groups. On the other hand, being younger, having a higher level of mental health, having a higher frequency of going out, and participating in community groups were identified as factors that predicted participants' recovery from social isolation. Major conclusions: Some demographic, mental, and social factors could relate to new incidences of social isolation and recovery from social isolation in community-dwelling older people. As aging is an irreversible phenomenon, and there is a limit to preventing all disorders, either building a safety net or introducing exchange programs to prevent social isolation are important interventions for older people.